2011
DOI: 10.1523/jneurosci.4153-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Beta-Range Coherence Is Highly Dependent on the Pre-stationary Motor State

Abstract: During steady muscle contractions, the human sensorimotor cortex generates oscillations in the beta-frequency range (15-30 Hz) that are coherent with the activity of contralateral spinal motoneurons. This corticospinal coherence is thought to favor stationary motor states, but its mode of operation remains elusive. We hypothesized that corticospinal beta-range coherence depends on the sensorimotor processing state before a steady force task and may thus increase after sensorimotor tuning to dynamic force gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…In a previous study (Omlor et al 2011), we showed that beta-range corticospinal coherence during isometric compensation of static force is highly dependent on the prestationary motor state: the beta-range CMC was higher after unpredictable frequency-and amplitude-modulated forces. These modulated forces induce higher computational load as reflected in the stronger cortical motor desynchronization (i.e., lower cortical motor spectral power) than predictable frequency-modulated forces.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…In a previous study (Omlor et al 2011), we showed that beta-range corticospinal coherence during isometric compensation of static force is highly dependent on the prestationary motor state: the beta-range CMC was higher after unpredictable frequency-and amplitude-modulated forces. These modulated forces induce higher computational load as reflected in the stronger cortical motor desynchronization (i.e., lower cortical motor spectral power) than predictable frequency-modulated forces.…”
mentioning
confidence: 78%
“…Furthermore, on the basis of the lower cortical motor spectral power (SP) during UF described in Omlor et al (2011), we predicted stronger cortical motor desynchronization during UF, which would be reflected in smaller cortical motor SP. We also expected a stronger cortical activation, as measured by the task-related desynchronization (TRD) computed by the SP during the task with reference to a baseline (Pfurtscheller 1992;Pfurtscheller and Andrew 1999;Pfurtscheller and Aranibar 1977).…”
mentioning
confidence: 91%
“…This is reflected in corticomuscular (EEG-MEG/EMG) coherence (Conway et al, 1995;Brown, 2000;Baker et al, 2006;Baker, 2007;Omlor et al, 2007Omlor et al, , 2011Mendez-Balbuena et al, 2012). Baker et al (2006) provided direct evidence that sustained afferent discharge from muscle receptors is coherent with central oscillations involved with sensorimotor processing.…”
Section: The Role Of the Peripheral Cutaneous Receptors And Of Musclementioning
confidence: 93%
“…For larger movements such as changes in length of muscles, angles of joints, the beta-CMC during the following rest phase was increased compared to after smaller movements (Witte et al, 2007). This pointed to a possible role of beta-CMC in re-calibration mechanisms Omlor et al, 2011). Increases in beta-CMC was also accompanied by improved compliance and decreased errors , which may suggest that increased beta-CMC improves integration of somatosensory information leading to better motor performance Witte et al, 2007;Omlor et al, 2011).…”
Section: Physiological Relevance Of Corticomuscular Coherencementioning
confidence: 95%
“…An experiment with varying motor tasks before a hold state showed that beta-CMC was modulated depending on the computational load of the preceding motor activity (Omlor et al, 2011). For larger movements such as changes in length of muscles, angles of joints, the beta-CMC during the following rest phase was increased compared to after smaller movements (Witte et al, 2007).…”
Section: Physiological Relevance Of Corticomuscular Coherencementioning
confidence: 99%